O atendimento socioeducativo de adolescentes em cumprimento de medida socioeducativa em meio aberto no município de Castro - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This research aims to analyze material, political, social, technical, ethical and institutional mediations present in the socio-educational care of adolescents in compliance with socio-educational measures in an open environment in the city of Castro-PR. Therefore, a historical contextualization of the guarantee of rights and the different forms of protection in the modern State was carried out (chapter one); the contours and contradictions of social protection for adolescents in Brazil were addressed (chapter two) and, finally, the socio-educational care of adolescents in compliance with socio-educational measures in an open environment in the municipality of Castro-PR was analyzed (chapter three). In order to achieve the proposed objective, it is based on a qualitative and exploratory nature, which was based on bibliographical and documentary research for theoretical support. A documentary analysis of the Individual Care Plans (PIAs) of the 32 adolescents in compliance with a socio-educational measure was carried out in an open environment in March 2020 at CREAS Neuza Aparecida de Freitas in the municipality of Castro- PR. Also, semi-structured interviews were applied with the research subjects, identified and selected from the document analysis and the technical indication responsible for socio-educational care. The application was limited to three professionals and three relatives of the adolescents in compliance with a socio-educational measure in March. It is noteworthy that adolescents are represented by the analysis of PIAs, as their construction is carried out from their speeches. For data analysis, we chose to use content analysis. The research results indicated that the constant changes that socioeducational care has undergone in the municipality throughout its history, including an attempt to implement an intersectoral and interdisciplinary municipal program that did not take place, hampered and still hinder the structuring of the service that at the time The current one does not have a minimum team to attend to the adolescents, making the execution and quality of the service difficult, given the complexity of the demands and the vulnerability profile of adolescents in conflict with the law. Regarding vulnerabilities, it was observed that they are expressions of the order of capital and affect the daily lives of adolescents and their families, which are permeated by various elements that hinder or prevent the guarantee of their rights and are expressed, for example, by violation of fundamental rights, such as education, health, work and leisure. The context of the municipality showed difficulties in articulation, especially in the intersectoral network, which demonstrates the weaknesses of other public policies that interface with socio-education. In this sense, it is understood as essential the minimum structuring and strengthening of the service in its intersectoral articulation in order to guarantee social protection for the affirmation of socio-education as a public policy at the municipal level.
Keywords: atendimento socioeducativo; vulnerabilidades; adolescentes em cumprimento de medida socioeducativa em meio aberto; serviços socioassistenciais; rede socioassistencial e intersetorial; socio-educational assistance; vulnerabilities; adolescents in compliance with socio-educational measures in an open environment; socio-assistance services; socio-assistance and intersetorial network; CNPQ::CIENCIAS SOCIAIS APLICADAS